2017
DOI: 10.1111/ijcp.12971
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing the quality of primary care referrals to surgery of patients with diabetes in the East of England: A multi-centre cross-sectional cohort study

Abstract: This study has shown that the quality of referral letters to surgical specialties for patients with DM in the East of England remain inadequate. There is a clear need for improving the quality of clinical data contained within referral letters from primary care. In addition, we have shown that the rate of referral for surgery for people with diabetes is almost 50% higher than the background population with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…The Joint British Diabetes Societies (JBDS) guidelines state the perioperative process should be seamless and that the patient should be involved in planning at all stages [2], yet failure of communication is often identified as a common issue in inpatient experiences [3] along with difficulty in identifying high-risk patients prior to surgery [2]. Primary care referrals often lack detail about diabetes, such as the patient's recent HbA 1c concentration or their glucose medication, and some fail to make mention of diabetes at all in the referral letter [4].…”
Section: Introductionmentioning
confidence: 99%
“…The Joint British Diabetes Societies (JBDS) guidelines state the perioperative process should be seamless and that the patient should be involved in planning at all stages [2], yet failure of communication is often identified as a common issue in inpatient experiences [3] along with difficulty in identifying high-risk patients prior to surgery [2]. Primary care referrals often lack detail about diabetes, such as the patient's recent HbA 1c concentration or their glucose medication, and some fail to make mention of diabetes at all in the referral letter [4].…”
Section: Introductionmentioning
confidence: 99%
“…Special mention should be made of the 14% (n = 24) of patients who proceeded to surgery without even having an HbA1C measured within the 6‐month preoperative period. Work published by Pournaras et al demonstrated that of 169 primary care referrals to secondary care for consideration of elective surgery, 23% (n = 38) did not mention the presence of existing diabetes . Furthermore, it showed that only 8% (n = 13) included an HbA1C reading in the referral letter.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of Diabetes Mellitus (DM) in the UK currently stands at 8.6%, affecting nearly 3.8 million people 1 and accounting for 10%-15% of patients undergoing surgery. 2,3 Furthermore, the prevalence of DM is predicted to rise by 50% over the next decade. 1,4 Poor perioperative glucose control has been associated with adverse outcomes and higher complication rates in almost every surgical speciality.…”
Section: Introductionmentioning
confidence: 99%
“…The referral letter to the surgical team should detail all relevant pathology and medication as well as the current HbA1c. Currently, this is poorly done . If diabetes is not optimally managed at the time of referral, advice from the diabetes team should be sought as soon as possible, to facilitate optimisation.…”
Section: Implications For Practicementioning
confidence: 99%
“…There is now increasing evidence that diabetes is a modifiable risk factor and that the care of the surgical patient with diabetes and pre‐diabetes can be optimised, with a subsequent decrease in complications and mortality. It is therefore imperative that a consultation request by primary care for a surgical opinion mentions diabetes in the referral letter; a recent study showed that the presence of diabetes was not included in over 22% of all referral letters for people with the condition .…”
Section: Introductionmentioning
confidence: 99%